HASIL BELAJAR SISWA MELALUI IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN BIOLOGI SMA KELAS X - Purba, Ika Rosenta; Damanik, Risjunardi; Sintana, Alika Dinda (Jurnal Metabio, 2024)
This research ains to determinan the influence of implementing Project Based Learning to determinan student learning oucomes. The research was cariied out with a queatitative approach using a Pree-test and  Poos-test  Control Group Desain research design and there werw 3 geoup  selected by random Assigment. The research population was seventeen tudent cosisting ot two classes, samples were taken using cluster random samping techniques, There is an influence of the Project Based Learning learning model on student before participacing in the Project Based  Learning model 66,14. Meanwile the avaragge score for the poostes class after following the Project Based Learning mode 80,86. Based on the result of the hypothesis test, it shows that count > Ttabel (2,574 >1,671). And for a probability value of 0,00 < 0,05, witch mwans Ha is accepted and H0 is rejected, it can be coccluded that there is a significant influence using the projrct abased learning outcome at Tamansiswa Pematangsiantar High School.